(untitled) (IJM: Journal of Multidisiplinary, 2024)
Endowment is a form of virtuous practice in Islam that provides continuous benefits even after the benefactor passes away. This concept is rooted in the belief that the rewards of endowment will continue to flow to the benefactor in the afterlife. Not only does this practice have positive spiritual impacts, but it also yields tangible benefits for society and the surrounding environment. This study employs a qualitative approach to delve into the understanding, experiences, and perspectives of individuals or groups regarding endowment. The methods utilized include Focus Group Discussions (FGD) and document analysis to gain deeper insights into the practices of endowment and philanthropy within the context of Islam. The findings of this research are expected to enhance understanding of the importance of endowment in fostering sustainable goodness within communities. By further exploring the concept of endowment, it is hoped that this study will encourage communities to actively engage in continuous virtuous deeds, thereby strengthening faith and fostering compassion towards others.